The effect of team games tournament model assisted by snakes and ladder on students’ conceptual understanding in mathematics - Wulandary, Triya; Nirawati, Resy; Safrihady, Safrihady (Journal of Didactic Mathematics, 2025)
This study evaluates the efficacy of the Team Games Tournament (TGT) model, augmented with snakes and ladders game media, in enhancing the conceptual comprehension and learning motivation of Grade 5 students at SDN 88 Singkawang. Employing a quantitative approach employing a quasi-experimental posttest-only control group design, the research encompassed all Grade 5 students through a total sampling strategy. The control group consisted of 23 students from class 5-A, while the experimental group included 24 students from class 5-B. Data was collected utilizing both test and non-test instruments, and assumption testing was conducted via the Chi-Square normality test and homogeneity of variance test. Independent samples t-test, effect size calculation, and percentage analysis were employed to analyze the data. The findings revealed a substantial disparity in conceptual understanding between the two groups. The experimental group demonstrated superior scores, as evidenced by t(45) = 5.61, p < 0.001, surpassing the critical value of ttable = 2.01. The effect size of 1.4 confirmed the pronounced impact of the TGT model coupled with snakes and ladders game media. Furthermore, students’ learning interest within the experimental group was categorized as high, with an average percentage of 82.1%. In summation, the integration of the TGT model with snakes and ladders game media significantly enhances both conceptual comprehension and learning motivation among Grade 5 students, particularly in the domain of mathematics, specifically fractions. These findings underscore the potential of combining cooperative learning models with game-based media to foster active engagement and profound understanding in elementary mathematics education.